Observation of the exceptional point in cavity magnon-polaritons - Dengke Zhang (Nature Portfolio, 2017)
Strong coupling between magnons and photons allows coupling of magnongs to qubits, suggesting that magnon-polaritons could find applications in quantum information. Here, Zhang et al. observe an exceptional point and spontaneous symmetry breaking in a cavity magnon-polariton system.